<u>Answer:</u>
![y = -\frac{2}{3}x + 490](https://tex.z-dn.net/?f=y%20%3D%20-%5Cfrac%7B2%7D%7B3%7Dx%20%2B%20490)
gradient = = ![-\frac{2}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7D)
y-intercept = ![490](https://tex.z-dn.net/?f=490)
<u>Step-by-step explanation:</u>
• The slope-intercept form of an equation takes the general form:
,
where:
m = slope,
c = y-intercept.
• We are given the equation:
![2x + 3y = 1470](https://tex.z-dn.net/?f=2x%20%2B%203y%20%3D%201470)
To change this into the slope-intercept form, we must make y the subject:
[subtract
from both sides]
⇒
[divide both sides by 3]
⇒ ![y = -\frac{2}{3}x + 490](https://tex.z-dn.net/?f=y%20%3D%20-%5Cfrac%7B2%7D%7B3%7Dx%20%2B%20490)
• Comparing this equation with the general form equation, we see that:
m = ![-\frac{2}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7D)
c =
.
This means that the gradient is
, and the y-intercept is
.